Digital Cognitive Behavior Modification Module to Reduce Cyberbullying Behavior - Yusri, Nada Fristy; Yeni Karneli; Netrawati (Journal of Education Technology, 2023)
Cyberbullying among teenagers is increasingly common and is disturbing the world of education. Cyberbullying has a severe negative impact on the psychological, emotional and social fields, which leads to fear, anxiety and suicide. This research aims to produce a product in the form of a digital cognitive behaviour modification module to reduce cyberbullying behaviour, which has been tested as valid and can be used by guidance and counselling teachers and counsellors. This research uses a type of research and development using the ADDIE procedural model. The module material was obtained from an analysis of students' cyberbullying behaviour needs; then, a module feasibility test was carried out by 2 material experts and 2 media experts. Usability test by 3 guidance and counselling teachers. The methods used to collect data are observation, interviews and questionnaires. The instrument used to collect data was a questionnaire. The techniques used to analyze the data are descriptive analysis and non-parametric analysis. The results of this research are that the digital cognitive behaviour modification module to reduce cyberbullying behaviour is in the very appropriate category from experts and has received results. The practicality test results of the digital module are in a very good class. It was concluded that the digital module prepared was suitable for implementation or use by guidance and counselling teachers and counsellors. The implication of this research is that the digital module developed helps counselors and guidance and counseling teachers in providing services to their clients.